Programmable flow injection: a versatile technique for benchtop and autonomous analysis of phosphate and silicate in seawater - Marine Lebrec; Maxime M. Grand (Frontiers in Marine Science, 2024)
High-resolution, autonomous monitoring of phosphate and silicate in the marine environment is essential to understand their complex dynamics and implications for the functioning of marine ecosystems. In the absence of dependable reagent-less sensors for these nutrients, leveraging established colorimetric techniques using miniaturized analyzers, such as programmable Flow Injection (pFI), offers the best immediate solution to meet oceanographic accuracy and precision standards. In this work, we further optimize the phosphomolybdate and silicomolybdate assays recently adapted for use with pFI, laying the groundwork for the technique’s use for long-term, autonomous operations. For both assays, we show that only a narrow range of acidities and molybdate concentrations can maximize sensitivity while minimizing salt effects. In addition, we demonstrate the stability of our optimized colorimetric reagent formulations, ensuring that analytical sensitivity remains within 10% of initial levels for at least 35 days of continuous use. We then applied our optimized protocols to produce oceanographically consistent phosphate and silicate profiles at the Hawaii Ocean Time Series (HOTS) and Southern Ocean Time Series (SOTS), respectively, which compared favorably against a reference method and historical data. Using certified reference materials for nutrients in seawater, we show that our pFI protocols, optimized for long-term operations, achieve a shipboard precision better than 6% and a relative combined uncertainty (k=1) of 4.5% for phosphate (0.45 - 2.95 µmol L-1) and 6.2% for silicate (2.2 to 103 µmol L-1). To demonstrate pFI’s potential as a versatile tool for autonomous monitoring, we report a five-day hourly phosphate time series at a coastal shore station in central California (n=121 analyses), examine phosphate uptake by seaweed at five-minute intervals at a seaweed aquaculture facility (n=103), and discuss a unique, high-resolution surface silicate transect spanning multiple frontal zones in the Australian sector of the Southern Ocean (n=249). These data, obtained using a commercially available pFI analyzer, confirm that pFI is a viable technology for autonomous monitoring of phosphate and silicate, paving the way for more ambitious, long-term deployments in a variety of settings.